2005
DOI: 10.1016/j.ejheart.2005.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Obese subjects with heart failure have lower N‐terminal pro‐brain natriuretic peptide plasma levels irrespective of aetiology

Abstract: N-terminal pro-brain natriuretic peptide (NT-proBNP) may be useful in the diagnosis of heart failure and ventricular dysfunction. Obesity is an independent cardiovascular risk factor. The purpose of this study was to measure NT-proBNP plasma levels in obese and non-obese subjects with heart failure and to compare levels in subjects with ischaemic and dilated aetiology.In this study, obese subjects had 63% lower NT-proBNP plasma levels than non-obese subjects ( p < 0.01). In multivariate analysis, BMI was inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 9 publications
(12 reference statements)
4
29
0
Order By: Relevance
“…The majority of studies [12,21,22] have shown a negative correlation between plasma BNP concentrations and obesity in adults, both male and female, with and without heart failure, compared to the normal BMI individuals. A similarly inverse association was confirmed recently for NT-proBNP and BMI [23,24] and this relation was considered a potential link between obesity and hypertension. The investigators reasoned that obese patients with lower BNP levels at given levels of cardiac wall stress might lose the vasodilatory benefit of a high BNP.…”
Section: Discussionsupporting
confidence: 73%
“…The majority of studies [12,21,22] have shown a negative correlation between plasma BNP concentrations and obesity in adults, both male and female, with and without heart failure, compared to the normal BMI individuals. A similarly inverse association was confirmed recently for NT-proBNP and BMI [23,24] and this relation was considered a potential link between obesity and hypertension. The investigators reasoned that obese patients with lower BNP levels at given levels of cardiac wall stress might lose the vasodilatory benefit of a high BNP.…”
Section: Discussionsupporting
confidence: 73%
“…BNP levels are generally lower despite higher LV end-diastolic pressures in the obese and people with metabolic syndrome, whether they have CHF or not. [119][120][121][122][123] However, if this is taken into account, BNP retains similar diagnostic significance in obese subjects as in non-obese subjects. 124 Exercise capacity is not a good guide to the origin of breathlessness, as morbid obesity and chronic heart failure are both associated with a similar reduction in exercise capacity, and decreasing exercise capacity is related just as strongly to an adverse prognosis in both groups.…”
Section: Diagnostic Difficultiesmentioning
confidence: 99%
“…Another potential limitation to the use of BNP is in patients who are obese (body mass index of 30 kg/m 2 or greater). Various studies (38)(39)(40)(41)(42) have demonstrated that BNP (and NT-proBNP) levels are lower in obese patients, with and without heart failure, than in nonobese comparators. The mechanisms behind lower circulating BNP levels in obese patients are unclear, but may include decreased production combined with increased clearance of BNP.…”
Section: Bnp Versus Nt-probnpmentioning
confidence: 99%